(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
In an increasingly globalized world, the need for medical students to learn foreign languages has become imperative for effective communication in international healthcare settings. This article explores innovative approaches to foreign language acquisition specifically tailored for medical students. By integrating technology, experiential learning, and interdisciplinary methods, the article examines how modern techniques can enhance language proficiency. It also addresses the challenges faced by medical students due to their demanding schedules and explores how these innovations can make language learning more efficient and relevant to their future careers. The study highlights key strategies such as immersive simulations, digital learning tools, and medical terminology-focused curricula.